Disruption of the thyroid hormone system and patterns of altered thyroid hormones after gestational chemical exposures in rodents – a systematic review - Forner-Piquer, Isabel; Baig, Asma H.; Kortenkamp, Andreas (Frontiers in Endocrinology, 2024)
We present a comprehensive overview of changes in thyroxine (T4) and thyroid stimulating hormone (TSH) serum concentrations after pre-gestational, gestational and/or lactation exposures of rodents to various chemicals that affect the thyroid hormone system. We show that T4 and TSH changes consistent with the idealised view of the hypothalamic-pituitary-thyroid (HPT) feedback loop (T4 decrements accompanied by TSH increases) are observed with only a relatively small set of chemicals. Most substances affect concentrations of various thyroid hormones without increasing TSH. Studies of altered T4 concentrations after gestational exposures are limited to a relatively small set of chemicals in which pesticides, pharmaceuticals and industrial chemicals are under-represented. Our risk-of-bias analysis exposed deficits in T4/TSH analytics as a problem area. By relating patterns of T4 -TSH changes to mode-of-action (MOA) information, we found that chemicals capable of disrupting the HPT feedback frequently affected thyroid hormone synthesis, while substances that produced T4 serum decrements without accompanying TSH increases lacked this ability, but often induced liver enzyme systems responsible for the elimination of TH by glucuronidation. Importantly, a multitude of MOA leads to decrements of serum T4. The current EU approaches for identifying thyroid hormone systemdisrupting chemicals, with their reliance on altered TH serum levels as indicators of a hormonal mode of action and thyroid histopathological changes as indicators of adversity, will miss chemicals that produce T4/T3 serum decreases without accompanying TSH increases. This is of concern as it may lead to a disregard for chemicals that produce developmental neurotoxicity by disrupting adequate T4/T3 supply to the brain, but without increasing TSH.